Writing herself into being : Quebec women's autobiographical writings from Marie de l'Incarnation to Nelly Arcan - Smart, Patricia, 1940- (McGill-Queen's University Press, 2017)
Quebec women's struggle for self and portrayal of their society in autobiographies, letters, and private diaries.